The effect of carbonate apatite membrane gelatin application on IL-1β level gingival crevicular fluid in chronic periodontitis patients - Pribadi, Indra Mustika Setia; Hendiani, Ina; Sartiono, Reynaldy (Universitas Padjadjaran, 2019)
Introduction: Apatite carbonate material plays an important role in bone tissue regeneration. The use of this membrane is expected to achieve better treatment success than those without additional therapy. The antimicrobial content in the apatite carbonate membrane can be used to support periodontal treatment of chronic periodontitis after scaling and root planing. The purpose of this research was to analyse the effect of carbonate apatite membrane gelatin application on the IL-1β level of the gingival crevicular fluid in chronic periodontitis patients. Methods: This research was a double-blind, randomised controlled trial method, with purposive sampling, and split-mouth design. The parameter was the IL-1β level in the gingival crevicular fluid before and after scaling and root planing. Carbonate apatite membrane gelatin was applied to the periodontal pocket on the test group after scaling and root planing. Data were analysed by the Wilcoxon test with a p-value < 0.05. Results: The reduction of IL-1β level gingival crevicular fluid on day-0 and day-30 on both groups showed significant value (p < 0.001). However, it showed no significant differences statistically, between the test group and the control group. Conclusion: Carbonate apatite membrane gelatin application might reduce the IL-1β level of the gingival crevicular fluid, but not showing a better reduction from the control group.Keyword: Carbonate apatite membrane gelatin, IL-1β, periodontal therapy